2012
DOI: 10.1002/cbf.2814
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and band 3 protein function in Liza aurata and Salmo irideus erythrocytes: effect of different aquatic conditions

Abstract: The aim of this study was to assess the effect of the different aquatic conditions on anion transport of fish erythrocytes through the measurement of the sulphate uptake operating from band 3, the determination of reduced glutathione (GSH) and oxidized glutathione (GSSG). To this purpose, blood samples of 30 Liza aurata and 30 Salmo irideus fishes were collected via caudal vein and washed with physiological buffer. Successively, erythrocytes suspended at 3% haematocrit were used to measure the SO(4) (=) influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Ozaydin et al () found that BPA significantly decreased the levels of GSH, SOD, GPx and CAT, and increased the levels of MDA in plasma of Wistar albino rats. In general, whenever Nile tilapia exposed to water pollution, it exerts metabolic mechanisms that help them for adaptation (Casella et al, ; Faggio et al, ; Fazio et al, ; Stephensen et al, ), detoxification (Pagano et al, ; Sheehan, Meade, Foley, & others, ;), and/or oxidative defense protection (Abdel‐Tawwab & Wafeek, ; Abdel‐Tawwab, El‐Sayed, Monier, et al, ; Geret & Bebianno, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ozaydin et al () found that BPA significantly decreased the levels of GSH, SOD, GPx and CAT, and increased the levels of MDA in plasma of Wistar albino rats. In general, whenever Nile tilapia exposed to water pollution, it exerts metabolic mechanisms that help them for adaptation (Casella et al, ; Faggio et al, ; Fazio et al, ; Stephensen et al, ), detoxification (Pagano et al, ; Sheehan, Meade, Foley, & others, ;), and/or oxidative defense protection (Abdel‐Tawwab & Wafeek, ; Abdel‐Tawwab, El‐Sayed, Monier, et al, ; Geret & Bebianno, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fish are able to live in different aquatic ecosystems including metal‐contaminated environments and they exert metabolic mechanisms that help them for adaptation (Casella et al., ; Faggio, Fedele, Arfuso, Panzera, & Fazio, ; Fazio et al., ; Stephensen et al., ), for detoxification (Pagano et al., ; Sheehan, Meade, Foley, & Dowd, ) and for the antioxidant protection (Geret & Bebianno, ). SOD is an important defence enzyme that catalyses the dismutation of O 2 , which produces H 2 O 2 that is converted to H 2 O and molecular oxygen by CAT (Qu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, because plasma membrane anion exchange is a nearly ubiquitous function in vertebrate cells, it has been studied in greatest detail in the human erythrocyte . However, several reviewers have also focused on band 3 in fish erythrocyte membranes and on the effects of different aquatic conditions on anion transport of fish erythrocytes through the measurement of the sulfate uptake operating from band 3 . Other authors also studied the erythrocyte anion transport showing the difference between nucleated and anucleated red blood cells (RBCs) .…”
Section: Introductionmentioning
confidence: 99%